Improving hospital flow ‘Ensiab Project’ - Yasser Alotaibi; Noura Alnowaiser; Ahmed Alamry (BMJ Open Quality)
Emergency department (ED) boarding is an indicator of less efficient hospital flow and is associated with longer inpatient length of stay, higher readmission rates and increased risk of mortality and medical errors. In addition to being associated with poor patient and staff satisfaction.This article describes the efforts of six tertiary care governmental hospitals in the Kingdom of Saudi Arabia that have enrolled in a collaborative improvement project to reduce ED boarding time.The hospitals implemented a multifaceted system intervention that included forming multidisciplinary flow improvement teams, implementing the National Health Service (NHS) SAFER patient flow bundle, visual management system and multidisciplinary ED bed huddles.By the end of the project, all hospitals significantly reduced ED boarding time with a pooled mean difference of – 7.1 hours (16.6 before, 9.5 hours after, p<0.001), reaching a pooled average of 2 hours in March 2020.Furthermore, by the end of the third learning session, all hospitals were able to achieve a boarding time below 6 hours. The enrolled hospitals also experienced an improvement in hospital flow process measures without any increase in 30-day readmission rates or bed occupancy rates.Our project demonstrates that implementing multifaceted system-wide interventions improves hospital flow and ED boarding time. Additionally, our project demonstrates a significant correlation between improvements in ED boarding time, daily consultant-led rounds and early discharge from inpatient units and time till discharge.